2007
DOI: 10.1016/j.jcis.2006.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lead on the sorption of phenol onto montmorillonites and organo-montmorillonites

Abstract: The effect of lead (Pb) on the sorption of phenol onto montmorillonite-based sorbents was studied using a batch equilibration method when phenol and Pb were sorbed simultaneously and either Pb or phenol was previously sorbed. The sorbents were Na + -, Ca 2+ -, hexadecyl trimethylammonium (HDTMA)-Na + -, and HDTMA-Ca 2+ -montmorillonites. Pb diminished the sorption of phenol largely onto Na + -or Ca 2+ -montmorillonites, while phenol had little effect on the sorption of Pb onto all sorbents. Pb had no effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 43 publications
2
14
0
1
Order By: Relevance
“…Clearly, the greatly elevated adsorption by SMZFA was attributed to the loaded HDTMA. It is known that aluminosilicate minerals modified with quaternary amines such as HDTMA can substantially enhance the adsorption of nonionic organic solutes from aqueous solutions [19][20][21][22][23][24][25][26][27][28]. The interaction mechanism is described as a partitioning process into the organic solvent-like hydrophobic phase created by the C-16 chain of HDTMA.…”
Section: Adsorption Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clearly, the greatly elevated adsorption by SMZFA was attributed to the loaded HDTMA. It is known that aluminosilicate minerals modified with quaternary amines such as HDTMA can substantially enhance the adsorption of nonionic organic solutes from aqueous solutions [19][20][21][22][23][24][25][26][27][28]. The interaction mechanism is described as a partitioning process into the organic solvent-like hydrophobic phase created by the C-16 chain of HDTMA.…”
Section: Adsorption Mechanismsmentioning
confidence: 99%
“…However, the influence of pH on phenol adsorption by surfactant-modified montmorillonite was evaluated by several groups. Dentel et al [20], Stapleton et al [21], and Yan et al [22] showed that the adsorption of phenols by surfactant-modified montmorillonite increased as the fraction of the neutral form of the solute increased with decreasing pH. In contrast, Zhou et al [23], Alkaram et al [24], and Al-Asheh et al [25] found that adsorption of phenols is increased with increasing pH value.…”
Section: Adsorption Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneous sorption of benzene and heavy metals (Pb, Cd, Zn and Hg) onto two organoclays, namely hexadecyltrimethylammonium bentonite clay (HDTMA-clay) and benzyltriethylammonium bentonite clay (BTEA-clay), has been reported [9], where the sorption of Pb, Cd, and Zn on both organoclays decreases in the presence of benzene. Similar research has been undertaken on the removal of Pb and chlorobenzene using HDTMA-clay [12], as well as the effect of Pb(II) on the sorption onto Na + -Mt and Ca 2+ -Mt and organoclays (HDTMA-Na-bentonite and HDTMA-Ca-bentonite) in the presence of phenol [13]. Therefore, work on characterizing the co-sorption of metals and organic contaminants on organoclay in the presence of organic solutes and metals is required to understand the co-sorption behaviours of heavy metals and organic pollutants and relevant mechanisms, which may help to sustain environmental standards for complex pollutants [13].…”
Section: Introductionmentioning
confidence: 80%
“…OMMT has previously been demonstrated by some researcher to be effective as a sorbent of phenol [27][28][29]. At the same time, phenol which is adsorbed by OMMT could be completely released into water and removed by microorganism.…”
Section: Introductionmentioning
confidence: 97%